Evaluation of immunomodulatory effect of Tinospora cordifolia leaf and stem on zidovudine induced immunotoxicity - Nageswari, G.; Reddy, A. Harinatha; Venkatappa, B. (International Journal of Scientific Research in Biological Sciences, 2018)
The present study was conducted to evaluate immunomodulatory effect of Tinospora cordifolia (T.C) leaf and stem extracts on zidovudine induced immunotoxicity. T.C leaves and stem was collected and three different extracts of stem and leaf (Aqueous, methanol, n-hexane) was prepared by Soxhlet extraction. Total 24 rats were used in the study. Rats were divided into 4 groups each of 6 rats. Group-I was treated with distilled water. Group-II rats received Zidovudine (500 mg/kg), Group-III given alcoholic extract of T.C stem (500 mg/kg) + Zidovudine (500 mg/kg) and Group-IV received alcoholic extract of T.C leaf (500 mg/kg) + Zidovudine (500 mg/kg). Physical and hematological and immunological parameters were measured at every alternative week. At the end of study rats were sacrificed under anesthesia. Thymus and spleen was collected and weighed. These findings suggest ameliorate effect of T.C leaf and stem extract on zidovudine induced immunotoxicity.